Keterkaitan antara Rumah Tangga Penerima Manfaat BLT dan Tingkat Konsumsi Pangan: Temuan dari Indonesia - Nadya Ahda (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2021)
The role of adequate nutrition in health and economic development, in general, has been recognized as very important and has been widely discussed in the previous literature. At the same time, research on the impact of the Unconditional Cash Transfer (UCT) program in Indonesia has also been frequently conducted. This study aims to evaluate the effect of UCT program acceptance status on household food consumption in Indonesia. The data used in this study is from the Indonesia Family Life Survey (IFLS), which allows this study to control various household socioeconomic characteristics that also influence household food consumption. The food consumption itself is proxied by the quantity of rice, chicken, and beef purchased during the last month. The estimation results show that rice consumption level differs significantly between beneficiary households and non-beneficiary households. Meanwhile, the difference is not statistically visible for chicken and beef consumption. This study then contributes to the existing literature implying UCT has a positive impact on the beneficiary household welfare in the short term.